Application of the strut-and-tie method for steel fiber reinforced concrete deep beams. (30th January 2017) - Moradi, M.; Esfahani, M. Reza
Highlights: Simple method for designing SFRC deep beams with opening is proposed. The proposed method is based on behavioral modeling of SFRC beams under tension in the context of STM. Influence of SFRC in behavior of deep beams with opening is investigated. Results experimentally validate the proposed method. Abstract: Using steel fiber reinforced concrete (SFRC) causes significant improvement in the behavior of deep beams with openings. This paper proposed a method for designing SFRC deep beams with opening, which was derived from previous studies on the behavior modeling of SFRC beams under tension and design principles of strut and tie method. To evaluate the proposed method, four large-scale specimens were used, which included two SFRC and two reinforced concrete deep beams with opening. Results of the test series illustrated the applicability of the proposed method.